Battle of the Bodkins : Max and the Midknights #2 - Peirce, Lincoln (New York : Crown Books for Young Readers, 2020)
"Max struggles at knight school, but when evil in the form of bodkins threatens Byjovia, Max reunites the Midknights to save the kingdom"--.
Ages 8-12.
Grades 4-6.
Keywords: Knights and knighthood -- Fiction; Adventure and adventurers -- Fiction; Magic -- Fiction; Middle Ages -- Fiction; Humorous fiction